Production model based on 5'S tools, visual control and SLP to reduce waste in a company in the poultry sector - Amoretti Magallanes, Mario Sergio (2025)
This work performs data analysis, as well as economic evaluation to validate whether the implementation of the engineering tools to be used is viable. For this purpose, the background, state of the art of the project, analysis and diagnosis of the problem were prepared using different improvement tools, which in this case are: 5's, visual control and Systematic Layout Planning (SLP). In addition, solution proposals were designed and developed for each tool and in this way validate the solution and economic validation; the impacts they may have on the different stakeholders relevant to the company and the sector. Thus, to achieve the results, pilot tests of 5's and visual control were developed. Where when carrying out an initial audit the result was 62% and after carrying out the pilot test there was an improvement that reached 86%; What it reflects is that if the company complies with the tools, there will be greater efficiency in it. Similarly, the use of the Arena simulator for the SLP tool also improved the technical gap approximately from 0,96% to 0,82%; However, the sector indicates that the ideal is 0,5%, but this will be achieved as the company adapts to the new changes. Likewise, by implementing these Lean Manufacturing and SLP tools, the monthly margin percentage increases by 2%, since monthly by reducing internal shrinkage there would be a monthly income of approximately $1 716,82 and if unplanned stops are reduced using visual control, you will have an income of approximately $4 539,86. For all of the above, it was concluded that, if the poultry company implements engineering tools, it will be more profitable, it will achieve cleaner spaces and, above all, collaborators more committed to their work.